Exploring the validity and reliability of online assessment for conversational, narrative, and expository discourse measures in school-aged children - Burchell, Diana; Bourassa Bédard, Vincent; Boyce, Keara; McLaren, Juliana; Brandeker, Myrto; Squires, Bonita; Kay-Raining Bird, Elizabeth; MacLeod, Andrea; Rezzonico, Stefano; Chen, Xi; Cleave, Pat; , FrEnDS-CAN (Frontiers in Communication, 2022)
The COVID-19 pandemic has created novel challenges in the assessment of children's speech and language. Collecting valid data is crucial for researchers and clinicians, yet the evidence on how data collection procedures can validly be adapted to an online format is sparse. The urgent need for online assessments has highlighted possible the barriers such as testing reliability and validity that clinicians face during implementation. The present study describes the adapted procedures for on-line assessments and compares the outcomes for monolingual and bilingual children of online and in-person testing using conversational, narrative and expository discourse samples and a standardized vocabulary test. A sample of 127 (103 in-person, 24 online) English monolinguals and 78 (53 in-person, 25 online) simultaneous French-English bilinguals aged 7–12 years were studied. Discourse samples were analyzed for productivity, proficiency, and syntactic complexity. MANOVAs were used to compare on-line and in-person testing contexts and age in two monolingual and bilingual school-age children. No differences across testing contexts were found for receptive vocabulary or narrative discourse. However, some modality differences were found for conversational and expository. The results from the study contribute to understanding how clinical assessment can be adapted for online format in school-aged children.